2015
DOI: 10.5099/aj150300148
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Imbalance in Pregnant Women with Malaria Parasitaemia

Abstract: Malaria in pregnancy is a life-threatening parasitic disease transmitted through the bite of female anopheles mosquitoes. Malaria is a preventable and treatable disease, yet it accounts for an estimated 660,000 deaths every year around the world mainly in Africa due to inappropriate management of imbalances in the electrolyte system of the patients. The aim of this study was to determine the severity of electrolyte imbalance in pregnant women with malaria parasitaemia. A total of 90 subject participated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
1
Order By: Relevance
“…The study also showed no significant correlation between the intensity of infection and the electrolyte levels. This finding contradicts the findings of [ 21 , 29 ] who reported electrolyte derangements among pregnant women, probably due to the variation in the pattern of malaria. However, Barber et al [ 30 ] also found normal electrolyte levels among malarious pregnant women.…”
Section: Discussioncontrasting
confidence: 99%
“…The study also showed no significant correlation between the intensity of infection and the electrolyte levels. This finding contradicts the findings of [ 21 , 29 ] who reported electrolyte derangements among pregnant women, probably due to the variation in the pattern of malaria. However, Barber et al [ 30 ] also found normal electrolyte levels among malarious pregnant women.…”
Section: Discussioncontrasting
confidence: 99%